Russia's Attitude Towards European Integration: Changing Approaches from Perception to Tough Opposition - Vira Shaturma (Vasyl Stefanyk Precarpathian National University, 2017)
In the article are highlighted the results of theoretical analysis of Russia's attitude towards European integration. The analysis unveiled the historical, cognitive and discoursive sources of Russia's unwillingness to join the EU. Researcher reveals some theories of scientists to study the problem of Russian national conception and its influence on Russian-EU relations. For depth scientific analysis the emphasis is made on evolution of Russia's perception towards European Union integration process.